Development of gold nanoparticles based immunosensor dipstick for the detection of cholera toxin - Rahman, Engku Nur Syafirah Engku Abd (Universiti Sains Malaysia, 2012)
Living in poverty stricken and poor sanitation countries often linked to water-borne diarrheal disease like cholera. The cholera toxin produced by toxigenic Vibrio cholerae strains are the etiology that results in profuse secretion of rice watery stool, leads to severe dehydration and shock. In this study, attempts were made to develop a dipstick assay for cholera toxin detection. Optimization of pH and amount of coating antibody for colloidal gold-anti-cholera toxin conjugation was done using particle flocculation assay. The control and test line concentrations were optimized and various blocking agents were tested to prevent the non-specific bindings on detection membrane. The stability of the dried gold conjugate was determined by optimizing the concentration of colloidal gold and sucrose. The culture for cholera toxin production was optimized by testing with different types of media, culture conditions, media volume, incubation time and temperature. A serially diluted pure cholera toxin was used for sensitivity test while specificity of dipstick was evaluated using others bacterial strains. Study showed that 0.20 mg/ml of goat antimouse and 5 pg/ml of GM, were found to be the optimum concentrations for control and test lines, respectively. Three percent BSA was found to be the optimal blocking reagent. The optimum consistency in colloidal gold release was showed by colloidal gold added with 3% BSA and 10% sucrose in 2 mM PBS, respectively. The 10 ml volume of YEP broth culture using AKI-SW method for 20 hours at 37°C were found to be the best method for cholera toxin production. The detection limit of dipstick sensitivity was found to be 10 ng/ml while specificity was found to be 100% with no invalid results. Thus, the dipstick assay permits rapid differentiation between toxigenic and non-toxigenic V. cholerae strains via cholera toxin detection that helps in surveillance of cholera cases.